Tera Gymnastic to Decrease Anxiety of Elderly - M Nancye, Pandeirot; Darmawan, Taufan Citra; Husni, Amin; Ratna Sawitri, Dian (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2022)
Introduction: The most common mental problem in the elderly is anxiety. The elderly is anxious due to lack of activity and rest. Elderly need activities that diverse, interesting, and easy to practice. Tera gymnastics therapy is type of exercise, easy to apply and does not require a lot of time. Tera gymnastics can be applied to the elderly as an interesting and easy alternative to exercise. The purpose of this study was to explain the effect of tera exercise on reducing anxiety in the elderly. Method: This study uses pre-experimental design with one group pre-post-test model. The study population was 43 elderly people who were in "‹"‹Boladangko Village, Central Sulawesi. The sample was 40 respondents with purposive sampling technique. The inclusions are 1) the elderly do not experience physical limitations 2) aged more than 60 years. Data collection using Depression Anxiety Stress Scale (DASS). The data analyzed by Wilcoxon test. Result: The results showed that most of the 37(92.5%) respondents stated that their anxiety was reduced. The results showed that 29(78.37%) respondents decreased 1 level of anxiety level, while the rest decreased 2 levels of anxiety level. The results of Wilcoxon test obtained Pvalue=0.009 indicating significant effect of giving tera exercise to the anxiety of the elderly. Conclusion: There is an influence between tera gymnastics and elderly anxiety, indicating that tera gymnastics can be applied to elderly as alternative to increasing elderly activities. Future research is expected to increase duration and combined with other methods to support better training.